Microbial Dissimilatory Sulfur Cycle in Acid Mine Water - Tuttle, Jon H. (1969)
Ferric, sulfate, and hydrogen ions are produced from pyritic minerals associated with coal as a result of autotrophic bacterial metabolism. Water carrying these ions accumulated behind a porous dam composed of wood dust originating at a log-cutting mill. As water seeped through the porous dam, it was enriched in organic nutrients which then supported growth and metabolism of heterotrophic bacteria in the water downstream from the dam. The heterotrophic microflora within and below the sawdust dam included dissimilatory sulfate-reducing anaerobic bacteria which reduce sulfate to sulfide. The sulfide produced caused the chemical reduction of ferric to ferrous ion, and black FeS precipitate was deposited on the pond bottom. A net increase in the pH of the lower pond water was observed when compared to the upper pond water. Microbial activity in the wood dust was demonstrated, and a sequence of cellulose degradation processes was inferred on the basis of sugar accumulation in mixed cultures in the laboratory, ultimately yielding fermentation products which serve as nutrients for sulfate-reducing bacteria. Some of the microorganisms were isolated and characterized. The biochemical and growth characteristics of pure culture isolates were generally consistent with observed reactions in the acidic environment, with the exception of sulfate-reducing bacteria. Mixed cultures which contained sulfate-reducing bacteria reduced sulfate at pH 3.0 in the laboratory with sawdust as the only nutrient. Pure cultures of sulfate-reducing bacteria isolated from the mixed cultures did not reduce sulfate below pH 5.5.